PENGELOLAAN KURIKULUM SALAFIYAH DALAM MENINGKATKAN KEMAMPUAN MEMBACA KITAB KUNING SANTRI DI PONDOK PESANTREN AL-JAUHAREN TANJUNG JOHOR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the management of the salafiyah curriculum in improving students’ ability to read classical Islamic texts (kitab kuning) at Pondok Pesantren Al-Jauharen Tanjung Johor. This research employs a qualitative approach using field study methods through interviews, observations, and documentation. The findings indicate that the salafiyah curriculum is managed through structured material planning, the implementation of traditional learning methods such as bandongan and sorogan, and gradual reading practices according to students’ levels. Consistent curriculum implementation, intensive guidance from instructors, and a supportive pesantren environment significantly enhance students’ mastery of nahwu-sharaf, their ability to read unvoweled Arabic texts, and their skill in analyzing the content of classical Islamic books. Challenges such as variations in students’ basic abilities and limited learning facilities are addressed through regular evaluation, individualized approaches, and strengthened reading exercises. Overall, the management of the salafiyah curriculum is proven effective in improving students’ kitab kuning reading skills and supporting their tafaqquh fi al-din development.